'The Rest is Silence': Psychogeography, Soundscape and Nostalgia in Pat Collins' Silence. Issue 2 (September 2015) - Mollaghan, Aimee
<x content-type="archive" xml:space="preserve">Abstract</x> Guy Debord defines the term psychogeography as 'the study of the precise laws and specific effects of the geographical environment, consciously organised or not, on the emotions and behaviour of individuals' (Debord 1955: 23). Similar to the belief of psychogeographers that the geography of an environment has a psychological effect on the human mind, proponents of acoustic ecology such as R. Murray Schafer hold that humans are affected by the sound of the environment in which they find themselves. Further to this, they examine the extent to which soundscapes can be shaped by human behaviour. Recently a body of Irish films has emerged that directly engages with the Irish soundscape and landscape on a psychogeographical level. Rather than using landscape as a physical space for the locus of action, these representations of the Irish landscape allow for an engagement with the aesthetic effects of the geographical landscape as a reflection of the psychological states of the protagonists. Bearing this in mind, this article examines how Silence (Collins 2012) arguably demonstrates the most overt and conscious incursion into this area to date. It specifically interrogates how the filmic representation of the psychogeography and soundscape of the Irish rural landscape can serve to express emotion, alienation and nostalgia, thus confronting both the Irish landscape and the weight of its associated history.